Craniometaphyseal Dysplasia: A review and novel oral manifestation - K. Martin; S. Nathwani; R. Bunyan (Elsevier, 2017)
Craniometaphyseal Dysplasia (CMD) is a sclerosing osseous dysplasia characterised by hyperostosis of craniofacial and long bones, resulting in distortion and cranial nerve palsies.We present a case report on the management of a 63 year old female with Craniometaphyseal Dysplasia. This report describes an additional clinical manifestation of hypercementosis, which although well recognised in other sclerosing osseous dysplasias, is not reported in the literature for Craniometaphyseal Dysplasia. We discuss established in vivo studies in mice which link the genetic mutations found in Craniometaphyseal Dysplasia to hypercementosis, and how this report describes the same manifestation in humans.This novel finding can aid the clinician in the management of patients with Craniometaphyseal Dysplasia, and complications that can arise in dentoalveolar surgery.